Efeito antifúngico de um inibidor de tripsina de sementes de Salvia hispanica L. contra cepas de Candida spp. resistentes de interesse clínico e avaliação da toxicidade in vitro - Nogueira, Francisca Cristiane (2023)
In recent years, serious fungal infections caused by Candida spp. have increased considerably, as well as episodes of resistance to conventional antifungals. This scenario has led to increased hospital treatment costs and patient mortality rates, which reinforces the need for new therapeutic strategies against microbial resistance. The present study evaluated the antifungal potential of a thermostable trypsin inhibitor isolated from Salvia hispanica L. (chia) seeds, here called ShTI, against Candida spp. resistant to fluconazole and in vitro toxicity in mammalian cells. To determine the antifungal effect of ShTI (0.02 to 8.22 μM) a microdilution assay was performed in broth in 96-well microplates against different strains of Candida. Combined treatments with ShTI and the conventional antifungal fluconazole (MIC/2 to MIC/32) were also tested to assess a possible synergistic effect. To evaluate the mode of action, strains of C. krusey (ATCC® 6258™) and C. albicans (strain 1) treated with ShTI were analyzed for cell membrane integrity and production of reactive oxygen species (ROS) by fluorescence microscopy, and cell morphology was evaluated by scanning electron microscopy (SEM). The toxicity of ShTI was evaluated by viability (MTT) and, cell morphological assays and alkaline comet assay in L929 mouse fibroblast cell lines, incubated with ShTI (8.65 - 17.3 μM). The results showed that ShTI was able to inhibit the growth of all tested strains: C. parapsilosis (ATCC® 22019), C. krusei (ATCC® 6258™) and fluconazole resistant-clinical strains: C. albicans (strain 1 and 2), C. parapsilosis (strain 1 and 2), and C. tropicalis (strain 1 and 2) (MIC = 8 .2 μM) besides exihibiting synergism against C. albicans (strain 1), (ICIF = 0.5) with complete alteration of the yeast morphological structure. Furthermore, ShTI promoted an increase in membrane permeability, overproduction of ROS indicated by fluorescence signals. Morphological changes with the formation of pores, pseudohyphae and extravasation of intracellular fluid, with the presence of pores C. krusey (ATCC® 6258™) and C. albicans (strain 1) cells. Furthermore, ShTI did not exhibit cyto- and genotoxic effects against murine fibroblasts at the tested concentrations. Results indicated that ShTI is a promising antifungal candidate, especially against clinically resistant species of C. albicans (strain 1), and has been shown to be a safe drug after preliminary in vitro toxicological assays in mammalian cells.